Pertumbuhan In Vitro Biji Jeruk Siam Pontianak (Citrus nobilis var. microcarpa) dengan Penambahan Ekstrak Jagung dan NAA pada Media MS - Felia Mulia Sari; Siti Ifadatin; Mukarlina Mukarlina (Universitas Islam Raden Rahmat, Malang, 2024)
Pontianak Siamese oranges (Citrus nobilis var. microcarpa) are one of West Kalimantan's leading commodities, which were first developed in the Tebas & Pemangkat area, Sambas Regency. Orange seeds have polyembryony, that is, there is more than one embryo in one seed, originating from a zygotic embryo and a somatic embryo. This research aims to determine the effect and appropriate concentration of adding corn extract and NAA to produce the best growth in Pontianak Siamese orange seed culture. This research used a completely randomized factorial design (CRD) with two factors. The first factor is corn extract (J) with 4 concentration levels, 0% (J0); 7,5% (J1); 10% (J2) and 12,5% ​​(J3). The second factor is NAA (N) with 4 concentration levels 0 M (N0); 10-7M (N1); 5.10-7M (N2) and 10-6M (N3). The data obtained was analyzed descriptively. The research results showed that the treatment of 12,5% ​​corn extract + 10-6M NAA (J3N3) was the best treatment for the time of sprout emergence and the fastest time for shoot emergence, namely 9,33 and 13,33 days. The treatment of 0% corn extract + 10-7M NAA (J0N1) produced the highest number of polyembryony shoots, namely 3,33 shoots. The 0% corn extract + 5.10-7M NAA (J0N2) treatment was the best treatment for the highest number of leaves on shoots from polyembryonic seeds, namely 2,16 pieces. The 7,5% corn extract + 10-6M NAA (J1N3) treatment and the 10% corn extract + 10-7M NAA (J2N1) treatment were the best treatments for the number of roots, namely 6 roots.